SOCS-2 gene expression at diagnosis does not predict for outcome of chronic myeloid leukemia patients on imatinib treatment. Issue 4 (21st March 2022) - Egeli, Damla Buket; Hanfstein, Benjamin; Lauseker, Michael; Pfirrmann, Markus; Saussele, Susanne; Baerlocher, Gabriela M.; Müller, Martin C.
Abstract: SOCS -2 gene expression at diagnosis has been suggested as a predictor of clinical outcome in chronic myeloid leukemia (CML). In this study SOCS-2 and GUS expression levels were determined by real-time PCR in pretherapeutic samples at diagnosis. First, three patient groups were compared after assessment at 48 months: optimal molecular responders ( n  = 35), patients with resistance to imatinib ( n  = 28), and blast crisis patients ( n  = 27). A significant difference in SOCS-2 gene expression at diagnosis was observed comparing blast crisis vs. resistant patients ( p  = 0.042) and optimal responders ( p  = 0.010). Second, a validation sample of consecutively randomized patients ( n  = 123) was investigated. No discriminative SOCS-2 gene expression cutoff could be derived to predict molecular or cytogenetic response, progression-free or overall survival. Although SOCS-2 gene was differentially expressed at the time of diagnosis in blast crisis patients when compared to other groups, a prognostic impact in consecutively randomized patients was not observed.